2019
DOI: 10.1113/jp278069
|View full text |Cite
|
Sign up to set email alerts
|

Role of zebrafish ClC‐K/barttin channels in apical kidney chloride reabsorption

Abstract: Key pointsr We have characterized the zebrafish clc-k and barttin proteins, demonstrating that they form a protein complex mediating chloride flux in a similar manner to their mammalian counterparts.r As in mammals, in zebrafish, clc-k and barttin are basically expressed in the kidney. Contrary to what is found in mammals, in zebrafish both proteins show an apical localization in the kidney.r We have generated the first knockout in zebrafish of a CLC protein. Lack of clc-k in zebrafish resulted in embryonic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…At first, the study of Pérez‐Rius et al . () found that zfclc‐k was expressed almost exclusively in the kidney. The in situ hybridization showed that zfclc‐k was located in the distal segment of the pronephros 24 h after fertilization.…”
Section: The Opportunity: Shared Characteristics Between Human and Zementioning
confidence: 97%
See 4 more Smart Citations
“…At first, the study of Pérez‐Rius et al . () found that zfclc‐k was expressed almost exclusively in the kidney. The in situ hybridization showed that zfclc‐k was located in the distal segment of the pronephros 24 h after fertilization.…”
Section: The Opportunity: Shared Characteristics Between Human and Zementioning
confidence: 97%
“…In a recent issue of The Journal of Physiology , Pérez‐Rius et al . () investigated the function of clc‐k–the only zebrafish orthologue of ClC‐Ka and ClC‐Kb–in kidney chloride reabsorption. This study found that clc‐k knockout caused lethality in zebrafish.…”
Section: The Opportunity: Shared Characteristics Between Human and Zementioning
confidence: 99%
See 3 more Smart Citations